2014
DOI: 10.1007/s00246-014-0919-1
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedure Prophylaxis Against Endocarditis Among United States Pediatric Cardiologists

Abstract: This study aimed to determine current practices regarding prophylaxis against infective endocarditis among pediatric cardiologists in the United States 5 years after publication of the most recent American Heart Association (AHA) recommendations. A descriptive, analytical, cross-sectional study was conducted from June 2012 to November 2012 in the format of an anonymous self-administered e-mailed questionnaire among pediatric cardiologists across the United States. The questionnaire inquired about demographic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…There was also a higher D score with respondents who are consultants versus nonconsultants, aged >40 years versus <40 years, and with experience of >10 years; however, none of these demographic features were statistically significant. Patel et al [14] reported similar findings that highly experienced pediatric cardiologists compared with their less experienced counterparts continue to administer preprocedural AP against IE even when it is not recommended.…”
Section: Discussionmentioning
confidence: 82%
“…There was also a higher D score with respondents who are consultants versus nonconsultants, aged >40 years versus <40 years, and with experience of >10 years; however, none of these demographic features were statistically significant. Patel et al [14] reported similar findings that highly experienced pediatric cardiologists compared with their less experienced counterparts continue to administer preprocedural AP against IE even when it is not recommended.…”
Section: Discussionmentioning
confidence: 82%
“…However, in some studies, the residual IE risk of some repaired CHDs appeared variously appreciated by specialized cardiologists such as perimembranous ventricular septal defect with no residual shunt or corrected tetralogy of Fallot with no residual shunt, inducing overprescription of IE AP [15][16][17]. Surprisingly, some cardiologists were less likely to recommend IE AP for patients at high risk for IE, mainly because some palliated cyanotic CHD cases are classified as being at high risk of IE by some authors [15] and at low risk for IE by others [16], such as Fontan palliation. However, our questionnaire was not intended to investigate such conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date no data have been produced for a population of general cardiologists. Only very specific data on pediatric cardiologists or congenital heart disease (CHD) specialists regarding the compliance with the 2007 AHA guidelines [14] are available [15][16][17]. All of them highlighted the correct identification of PCCs at high risk of IE by the cardiologic populations surveyed but all of them underlined IE AP overprescription for PCCs at moderate risk of IE that no longer require IE AP or for some PCCs with a low risk for IE with no indication for IE AP.…”
Section: Introductionmentioning
confidence: 99%
“…The primary antibiotic prophylaxis recommendations for placement of non-valvular cardiovascular devices advice that: "Because of the low incidence of infection for many of the devices, evidencebased data have not been collected that prove efficacy." Despite these recommendations, several human cardiologists and institutions do not follow the published guidelines and do administer prophylactic antibiotics (Weber et al, 2008;Shanson, 2010;Patel et al, 2014;BehjatiArdakani et al, 2015;Gillett et al, 2015).…”
Section: Discussionmentioning
confidence: 99%